Clonagem, sequenciamento e expressão do gen da lectina (Con Br) de sementes de Canavalia brasiliensis - Grangeiro, Thalles Barbosa (1996)
The effect of several glucose/mannose specific lectins from Diocleinae legumes on the survivorship of Nilaparvata lugens was investigated. The gene coding for the most insecticidal lectin was cloned, sequenced and expressed in Escherichia coli cells. In addition, the molecular and three-dimensional structure of the lectin with the best insecticidal properties were investigated by N-terminal sequencing, mass spectrometry and X-ray crystallography. Lectins from 9 Diocleinae species (genera Canavalia, Cratylia and Dioclea) were incorporated in artificial diet (0,1 %, m/v) and evaluated for their insecticidal properties against the Rice Brown Planthopper, Nilaparvata lugens, the most destructive pest of rice crop in Asia. AlI the lectins had insecticidal properties with different degrees of antimetabolic efIect. Con Br was the most toxic protein and caused the greatest reduction in the average survival time of N.lugens nymphs at the 0,1 % (m/v) leveI. On the other hand, Con Br did not show any significant deleterious effect on the growth and development of the pitch potato aphid, Aulacorthum solani. lndeed, Con Br (0,1 %, m/v) produced a significant (P<0,001) probiotic response on this insect by increasing the average survival time in relation to that observed with aphids fed on a control diet. However, the most dramatic probiotic effect of Con Br was observed by the stimulation of nymphs production by A.solani adults reared on a diet containing 0,1 % (m/v) of lectin. The gene coding for Con Br was amplified by PCR, cIoned and its complete nucleotide sequence was determined. The Con Br gene has an open reading frame of 870 bp and codes for a polypeptide with 290 amino acid residues corresponding to pre-pro-Con Br, the translational primary product. Taking into account the structural similarity between Con Br and Con A genes, the biosynthesis of Con Br involves similar post-translational events that have been described for Con A. The occurrence of 2 isoforms for the mature intact Con Br polypeptide was detected by N-terminal sequencing and mass spectrometry analysis of the protein fractions found in native Con Br. Thus, Con Br seems to be a mixture of isoforms which in part may arise by the transcription of very related genes. Con Br polypeptide chain folds in a three-dimensional slruclure almost identical to that determined for Con A. However, Con Br quaternary structure is slightly more open, which may cause subtle differences in the carbohydrate fine specificity of Con Br in relation to Con A. Therefore, Con Br may recognize very small topological changes in the structure of carbohydrates moieties on the cell surface receptors. This differences seem to be irrelevant for their insecticidal effects on N.lugens, although they may explain why Con Br and Con A have produced, in many other living systems, the same biological response but with different intensities.